Extended Conformable K-Hypergeometric Function and Its Application - Maham Abdul Qayyum; Aya Mohammed Dhiaa; Abid Mahboob; Muhammad Waheed Rasheed; Abdu Alameri (Advances in Mathematical Physics)
The extended conformable k-hypergeometric function finds various applications in physics due to its ability to describe complex mathematical relationships arising in different physical scenarios. Here are a few instances of its uses in physics, including nuclear physics, fluid dynamics, quantum mechanics, and astronomy. The main objectives of this paper are to introduce the extended conformable k-hypergeometric and confluent hypergeometric functions by utilizing the new definition of the α,k-beta function and studying its important properties, like integral representation, summation formula, derivative formula, transform formula, and generating function. Also, introduce the extension of the Riemann–Liouville fractional derivative and establish some results related to the newly defined fractional operator, such as the Mellin transform and relations to extended α,k-hypergeometric functions.